Revisión bibliográfica de los protocolos de manejo de biocontroladores (coccinélidos) en su captura, aislamiento y propagación Salache-Ceypsa 2020-2021. - Llumiquinga Cumbajin, Jessica Isabel (2021)
This research carries out the analysis and systematization of the protocols for the capture, isolation, and propagation of Coccinellidae since Ecuador does not have the necessary information for the breeding of these insects, which are considered beneficial for agriculture since their main activity is feeding on insects such as aphids and mealybugs. The methodology used for the research was based on monitoring, selection of documents, database, bibliographic management, and systematization. It was obtained due to six propagation methods, two isolation methods, and two propagation methods for Coccinellidae. The information obtained will help future researchers, farmers, and people interested in the subject to carry out adequate management of Coccinellidae.